Sistem Informasi Poin Kegiatan Mahasiswa Berbasis Website pada Universitas Nahdlatul Ulama Lampung - Rudi Hartono; Kusuma Wardany (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
As one of the graduation criteria at Nahdlatul Ulama University Lampung, student activity point management requires a reliable system. Currently, the manual mechanism implemented still encounters obstacles in the form of data inaccuracy and a lengthy verification process. This research aims to build a website-based Student Activity Point Information System to improve the quality of data management. Software development was carried out using the Waterfall model, starting from the analysis stage, design using UML, technical implementation (HTML, CSS, PHP, MySQL), to the functional testing stage. Through this system, students can submit activities online, while the administrator can validate and print point reports automatically. Based on the results of the Black Box test, all features in the system operate as designed. The presence of this system provides a more accurate and efficient solution, making it a credible support tool for the student affairs department. This system is expected to provide a more efficient and accurate solution in student activity point management, as well as support smooth administration and improve the quality of student affairs department services.